The effect of good corporate governance on tax avoidance - Oktavia, Amelia Ivon; Nurlaela, Siti; Siddi, Purnama (INOVASI, 2021)
This study aims to determine the effect of corporate governance on tax avoidance of property companies listed in the Indonesia Stock Exchange. This research is a quantitative descriptive study. The population in this study was obtained from the Indonesia Stock Exchange website www.idx .go.id, amounting to 48 1jsted companies, the type of data used in this study is secondaryidata.  The data  collection technique  used in  this research  is  documentation1j.  Data analysis in this studyiincludes multiple lineariregression analysist, t test, and the coefficient of determination1j.  The results showed  that:  The variable  of institutional ownership,  the number  of commissioners and the percentage of independent commissioners did not have a sign1jicant effect on tax avoidance, with a negative coefficient, and the variable number of audit committees had no significant effect on tax avoidance, with a positive coefficient.